Pengaruh Latihan Kekuatan Otot Kaki Terhadap Kecepatan Renang Gaya Kupu- Kupu Pada Atlet Bhayangkara Swimming Klub Bengkulu Selatan - Mardini, Septia; Martiani, Martiani; Anggara, Deffri (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
The purpose of this study was to determine the effect of leg muscle strength training on butterfly style swimming speed in athletes of Bhayangkaran Swimming Club South Bengkulu. This type of research is experimental research. This type of sample uses the Total Sampling technique. The sample of this study amounted to 15 Bhayangkaran Swimming Club athletes. The initial test was conducted by 16 people, the highest score was 18.26, the lowest score was 21.41, the average (mean) was 19.64 and the standard deviation was 1.08 then the final test the highest score was 18.12, the lowest score was 21.18. average (mean) 19.44, standard deviation (standard deviation) 1.06. So that the initial test average of 19.64 increased to 19.44. The instrument used in this study is butterfly style speed Based on pre test and post test data on butterfly style speed, the results of the normality test were obtained, all of which were normally distributed data. Furthermore, the t test results show tcount: 5.71> t table: 2,131. So this value indicates that leg strength training has a significant effect on increasing butterfly style speed. Thus the hypothesis that reads there is an effect of leg strength training on butterfly style swimming speed in athletes of bhayangkaran swimming club south bengkulu ‘ is accepted.